Mengatasi Kejenuhan Suami-Istri Perspektif Ulama Mazhab - Maloko, M. Thahir; Rahman, Arif (Universitas Islam Negeri Alauddin Makassar, 2020)
Making family in harmony is not as easy as we say. There are many obstacles faced by members of the family that sometimes make them bored. Those obstacles can be such as; business, different opinion, the presence of